Cut off from new competition: Threat of entry and health care quality - Eduard Brüll; Davud Rostam-Afschar; Oliver Schlenker (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study how the threat of entry affects service quantity and quality of general prac- titioners (GPs). We leverage Germany's needs-based primary care planning system, in which the likelihood of new GPs reduces by 20 percentage points when primary care coverage exceeds a cut-off. We compile novel data covering all German primary care regions and up to 30,000 GP-level observations from 2014 to 2019. Reduced threat of entry lowers patient satisfaction for incumbent GPs without nearby com- petitors but not in areas with competitors. We find no effects on working hours or quality measures at the regional level including hospitalizations and mortality.
Keywords: I11; I18; J44; J22; L10; L22; R23; 330; Entry regulation; general practitioners; healthcare provision; threat of entry; regression discontinuity design